Pengaruh Model Project Based Learning Materi Ragam Budaya Terhadap Hasil Belajar Kognitif Siswa Kelas IV-B SDN Tunjung 1 Burneh - Silviya Ayu Lestari; Aditya Dyah Puspitasari (Mataram University, 2026)
This study aimed to determine the effect of implementing the Project Based Learning model on the cognitive learning outcomes of fourth-grade B students in the topic of cultural diversity at SDN Tunjung 1 Burneh. This study was motivated by a teacher-centered learning process, limited student engagement in classroom activities, and students' average learning outcomes that did not meet the minimum mastery criteria. This research employed a quantitative approach using a pre-experimental method with a One Group Pretest-Posttest Design. The sample consisted of 26 students selected through a purposive sampling technique. Based on the results of the hypothesis test, the obtained value of Z table was greater than Z table (4.014 > 1.96), and the Asymp. Sig. (2-tailed) value was 0.000, which was lower than the significance level of 0.05. Therefore, H₀ was rejected and Hₐ was accepted. These findings indicate a significant difference in students' learning outcomes before and after the implementation of the treatment. Since the significance value was lower than the predetermined significance level, it can be concluded that the Project Based Learning model had a significant effect on the cognitive learning outcomes of fourth-grade B students in the topic of cultural diversity at SDN Tunjung 1 Burneh.